CLASSROOM COMMUNICATIVE STRUCTURE: EXCHANGE STRUCTURE IN EFL CLASS IN PUBLIC SENIOR HIGH SCHOOL 3 MOJOKERTO - Reza Fitri Rafsanjani; Ni Ketut Mirahayuni (Anaphora : Journal of Language, Literary, and Cultural Studies, 2018)
This article reported the study about classroom communicative structure between teacher and students in English class in Public School High School 3 Mojokerto. This study aims to identify the elements of minimal exchange structure and general exchange structure in communication in classroom. This study uses minimal exchange structure theory of Strenstrom (1994) by qualitative descriptive method. Data in this study are obtained from the recording of conversation among teacher and students of XI grade in Speaking class. The result shows that there are three (3) types  of act as the element of exchange structure:  Initiating, Responding, dan Following-Up (I-R-F). Minimal exchange structure  consists of: Initiating-Responding (I-R) or Initiating-Responding-Following Up (I-R-F). General structure of exchange in classroom situation consists of: greeting, followed by any kinds of functions such as giving information, giving order, and asking question. In conversation, teacher tends to has initiative to start it, meanwhile, the students tend to give respond by doing activity (evade) which are instructed by the teacher. The students sometimes did not answer the question, therefore teacher keeps the conversation going by undergone initiative actions such as giving information, asking question or giving instruction. This study shows that teacher has power to supervise and keep going the class activity.  It is needed to do further study  on power aspect in classroom communication.